Pain and depression are associated with both physical and mental fatigue independently of comorbidities and medications in primary Sjögren's syndrome. Issue 1 (24th April 2019) - Hackett, Kate L; Davies, Kristen; Tarn, Jessica; Bragg, Rebecca; Hargreaves, Ben; Miyamoto, Samira; McMeekin, Peter; Mitchell, Sheryl; Bowman, Simon; Price, Elizabeth J; Pease, Colin; Emery, Paul; et al.
Abstract : Objectives: To report on fatigue in patients from the United Kingdom primary Sjögren's syndrome (pSS) registry identifying factors associated with fatigue and robust to assignable causes such as comorbidities and medications associated with drowsiness. Methods: From our cohort (n = 608), we identified those with comorbidities associated with fatigue, and those taking medications associated with drowsiness. We constructed dummy variables, permitting the contribution of these potentially assignable causes of fatigue to be assessed. Using multiple regression analysis, we modelled the relationship between Profile of Fatigue and Discomfort physical and mental fatigue scores and potentially related variables. Results: Pain, depression and daytime sleepiness scores were closely associated with both physical and mental fatigue (all p ≤ 0.0001). In addition, dryness was strongly associated with physical fatigue (p ≤ 0.0001). These effects were observed even after adjustment for comorbidities associated with fatigue or medications associated with drowsiness. Conclusions: These findings support further research and clinical interventions targeting pain, dryness, depression and sleep to improve fatigue in patients with pSS. This finding is robust to both the effect of other comorbidities associated with fatigue and medications associated with drowsiness.